RESEARCHING THE DYNAMICS OF THE AGING PROCESS - Abdullaev G‘ofurjon Raximjonovich; Ikramova Nodira Maxmudovna (American Journals Publishing, 2023)
Aging is a complex process that leads to changes in all the systems of the body and all the functions of the person; however, aging develops at different rates in different people, and chronological age is not always consistent with biological age. Studies from the basic biology of aging using laboratory animals - and now extended to human populations - have led to the emergence of theories to explain aging. While there is no single “key” to explain aging, these studies have demonstrated that the rate of aging can be slowed, suggesting that targeting aging will coincidentally slow the appearance and/or reduce the burden of numerous diseases and increase health span (the portion of life spent in good health). Aging is associated with changes in dynamic biological, physiological, environmental, psychological, behavioral, and social processes. Some age-related changes are benign, such as graying hair.
Keywords: Geographic regions, basic biology of aging, mechanism of aging, psychological factors, the effects of exercising.